Prevalence of musculoskeletal disorders among non-occupational motorcyclists - K. JOTHI PRASANNA; J. NARENDRAKUMAR; M. MANIVANNAN; V.P.R. SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2017)
Musculoskeletal disorders are an increasing healthcare issue globally, being the second leading cause of disability.The studyobjective was to determine the prevalence of musculoskeletal disorders among non-occupational motorcyclist. Study design was prospective,study type was observational type, sampling method was convenient sampling, sample size was 100subjects, study setting was on general access the prevalence of musculoskeletal disorders among non-occupational motorcyclists.Public between 20-35years of both genders with driving experience of above 1year and driving duration of 2hours/day and were given a format of STANDARDIZED NORDIC MUSCULOSKELETAL DISCOMFORT QUESTIONNAIRE which depicts the prevalence of musculoskeletal disorders among non-occupational motorcyclist. Results were analyzed by using 1BM SPSS version 20.0 software. STANDARD NORDIC MUSCULO SKELETAL DISCOMFORT QUESTIONNAIRE values were applied to find out the prevalence of musculoskeletal discomfort in different areas of the body.The study concluded that Lower back (65%), neck (57%) and wrist(31%) are most common sites of musculoskeletal disorders among non-occupational motorcyclist in the past 12 months.